Lesões coronárias em pacientes com doença pulmonar obstrutiva crônica (GOLD I a III) e doença arterial coronária suspeita ou confirmada - Mota, Igor Larchert (2018)
BACKGROUND: Systemic inflammation is the pathophysiological link between coronary artery disease (CAD) and chronic obstructive pulmonary disease (COPD). However, the influence of underdiagnosed COPD on patients with suspected or diagnosed CAD is unknown. Therefore, the objective was to evaluate the degree of coronary involvement in COPD patients with suspected or confirmed CAD. Methods: For this cross-sectional study which we carried out March 2015 and June 2017, 210 outpatients with suspected or confirmed CAD were concomitantly underwent spirometry and coronary angiography or multidetector computed tomography. Two groups were defined: with and without COPD. Size, site, extent, and calcification of the coronary lesions, and the severity of COPD were analyzed. Results: COPD patients (n=101) presented: higher frequency of obstructive coronary lesions ≥ 50% 72 (71.3%), multi-vessels 29 (28.7%), of the left main 18 (17.8%), atherosclerotic plaques more calcified and higher Agatston coronary calcium score than the patients without COPD (p < 0.0001). The greater COPD in the GOLD stages, the more severe the CAD and the more calcified the coronary plaques (p < 0.0001). However, there was no difference between the two groups with respect to the main risk factors for CAD. In the univariate analysis, the COPD and the male gender have been risk predictors for CAD. In the multivariate analysis adjusted to COPD was independent predictor of obstructive CAD (odds ratio 4.78; CI 95% 2.21-10.34; p < 0.001). Conclusion: In patients with suspected or diagnosed CAD, the COPD was associated with a higher severity and extent of coronary lesions, calcific plaques, and elevated calcium score independently of the established risk factors for CAD. In addition, the more severe the COPD, the greater the severity of coronary lesions and calcification.